MODIFYING DICE BOARD GAME FOR TEACHING SPEAKING - Hidayaturrohmaniyah Hidayaturrohmaniyah; Adi Yusuf (Universitas Pesantren Tinggi Darul Ulum Jombang (Unipdu), 2022)
Dice Board Game is a type of modified board game that aims to encourage students to have interactive communication while learning through games. It is suggested that teaching materials should meet the needs of students. However, the suitability of teaching materials is often not considered. Therefore, it is necessary to design a media that can provide more opportunities for students to build their interactions as they need to acquire speaking skills. The design of this study is based on design-based research as proposed by Akker et al. In this study, in-depth interviews with teachers were conducted to find out the needs of students. In addition, observations were made on the syllabus and materials for media development. In addition, media implementation and interviews with English teachers were observed to assess the implementation and quality of the Dice Board Game. The results showed that the Dice Board Game media could motivate students to speak more. In addition, it was found that the activity met the practicality of speaking learning.